Education and Marriage as Protective Factors Against Homicide Mortality: Methodological and Substantive Findings from Moscow - Pridemore, William Alex (Journal of quantitative criminology, 2004)
This study examines the protective effects of education and marriage against homicide mortality in Russia. Individual data are obtained from death records and population data from the 1994 micro-census, and differentials in mortality from homicide are estimated employing two different methods: a straightforward approach using census data and proportional mortality analysis. We find that the latter underestimates the impact of education on homicide mortality. Despite differences in effect sizes, however, both methods reveal a significantly higher risk of homicide victimization for those that are unmarried and less educated. We conclude that education and marriage likely provide social capital and coping skills that protect individuals against violent victimization, even during times of dramatic social change and dire economic circumstances such as those faced in transitional Russia.